Overconfidence and prejudice - Paul Heidhues; Botond Kőszegi; Philipp Strack (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We develop a model in which an overconfident agent learns about groups in society from observations of his and others' successes. In our model, both the agent's information and his beliefs are multi-dimensional, allowing us to study interactions between different views. Overall, society always exhibits an in-group bias - the average person sees his group relative to other groups too positively - but this general tendency toward prejudice exhibits systematic comparative-statics patterns. First, a person is most likely to have negative opinions about other groups he competes with. Second, while information about another group's achievements does not lower a person's prejudice, information about economic or social forces affecting the group can, and personal contact with group members has a beneficial effect that is larger than in classical settings. Third, the agent's beliefs are subject to "bias substitution," whereby forces that decrease his bias regarding one group tend to increase his biases regarding unrelated other groups. Methodologically, to make our analysis of interdependent multi-dimensional beliefs possible, we develop tools for studying learning under high-dimensional misspecified models.
Keywords: D01; D83; D91; 330; beliefs; prejudice; inter-group beliefs; overconfidence; misspecified learning